1982
DOI: 10.1152/ajpgi.1982.242.2.g89
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate loss of glucocorticoid responsiveness by intestinal enzymes during postnatal development

Abstract: Jejunal sucrase is known to display glucocorticoid responsiveness from birth through day 17 but not beyond that age. The aim of the current study was to determine whether this abrupt loss of responsiveness was shared by maltase, lactase, and acid beta-galactosidase. Glucocorticoid concentrations were manipulated by both adrenalectomy (ADX) and by administration of cortisone acetate (CA). Surgery or treatment was performed on each day from 16--22 days of age. Maltase activity was reduced by ADX at day 18 and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 0 publications
5
20
0
Order By: Relevance
“…The containers were reweighed to the nearest 0.1 mg and stored at -20" C. Analyses. After homogenization in deionized water, the mucosa was assayed for lactase, sucrase, and maltase activities as previously described (14,15). In brief, after the homogenate was incubated at 37" C with the appropriate substrate, the liberated glucose was measured using a glucose oxidase reagent (Worthington Statzyme 500, Cooper Biomedical, Freehold, NJ).…”
Section: Animals Hanford Miniature Pigs (Charles River Breedingmentioning
confidence: 99%
“…The containers were reweighed to the nearest 0.1 mg and stored at -20" C. Analyses. After homogenization in deionized water, the mucosa was assayed for lactase, sucrase, and maltase activities as previously described (14,15). In brief, after the homogenate was incubated at 37" C with the appropriate substrate, the liberated glucose was measured using a glucose oxidase reagent (Worthington Statzyme 500, Cooper Biomedical, Freehold, NJ).…”
Section: Animals Hanford Miniature Pigs (Charles River Breedingmentioning
confidence: 99%
“…Some studies have found that the effects of a short (2-3day) undernourishment on digestive function in altricial birds can be compensated for relatively quickly (Lepczyk et al, 1998;Brzęk and Konarzewski, 2004) (but see Konarzewski et al, 1996). However, in many organisms the responsiveness of digestive physiology to external factors decreases during ontogeny (Henning and Leeper, 1982;Toloza and Diamond, 1990), which can limit the potential for reversible plasticity after fledging. Similarly, in some organisms even a very short period of diet manipulation may permanently influence digestive physiology (Geurden et al, 2007) (see also Patel and Srinivasan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is known that gastrointestinal (GI) synthesis of alkaline phosphatase in mice was increased by cortisone (Moog, 1953) or corticotrophin (ACTH) (Moog and Ford, 1957), and decreased after adrenalectomy (Moog, 1953) or hypophysectomy (Hinni and Watterson, 1963). Henning and Leeper (1982) and Arsenault and Menard (1984) reported that hydrocortisone induced the appearance of sucrase activity and increased activities of trehalase, glucoamylase, lactase and alkaline phosphates in the small intestine of the suckling rodents. Hydrocortisone also acts directly on the differentiation 694 J. TUR et al of the intestinal brush border membrane of the mouse.…”
Section: Introductionmentioning
confidence: 99%